Final Evaluation of a Real-Time Data Adaptation Tool for Automated Machine Learning - Devyani Dey,; Jeetendra Singh Yadav, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper presents a Real-Time Data Adaptation Tool designed to enhance the performance, stability, and automation of machine learning systems operating under continuously evolving data conditions. The proposed framework integrates automated preprocessing, concept drift detection, noise reduction, and dynamic hyperparameter optimization to maintain high model accuracy in real-time environments. Simulation results demonstrate that the tool achieves a significant 14–18% improvement in model performance, reduces latency to 45–60 ms, and outperforms recent state-of-the-art methods in accuracy, efficiency, and automation. Comparative analysis further validates the tool’s capability to support continuous learning pipelines with minimal manual intervention, making it suitable for modern AI-driven applications.
Keywords: Real-time data adaptation; automated machine learning; concept drift; performance optimization